PENGELOLAAN LINGKUNGAN SUNGAI BERDASARKAN SUMBER PENCEMARANAN DI SUNGAI CITARUM STUDI KASUS KELURAHAN TANJUNG MEKAR - Nadia Paramita; Sari Sekar Ningrum (Universitas Trisakti, 2020)
The Citarum River is a very vital and strategic river, where 80% is consumed by community watershed in DKI Jakarta, so that this creates environmental and health problems in Citarum river. The most common problem is the presence of waste consisting of factory, hotel and hospital waste as well as domestic waste, siltation, embankment problems and final processing sites that are harmful to health. The source of pollution of the Citarum River consists of 6.543 Ha including critical land due to forest encroachment, there is erosion of 31.4% in the upstream citarum area, 400 tons of cow dung from 29,000 head of cattleare dumped into the Citarum river. From 1500 industries that dispose of chemical waste (280 tons/day), it can be seen 500,000 m3/year of waste entering the Citarum river. Results Monitoring of the water quality of the Citarum River shows that Citarum River water has not been able to meet the water quality standards that have been determined based on SK. Governor of West Java No. 39/2000. The decrease in water quality was caused by an increase in pollutant load originating from the population, industrial development, extensification and intensification of agricultural land, fisheries development, livestock pollution and mining and excavation exploration. This community service aims to prove that where appropriate human resources and appropriate technology play an important role in environmentalmanagement around the Citarum River. The solution offered in this community service program is to analyze a system of domestic waste and wastewater management that is easily applied by community especially on the river banks in supporting community-based environmental governance.